Trust, guanxi, and cooperation: a study on partner opportunism in Chinese joint-venture manufacturing. Issue 1 (5th February 2018) - Xue, Jinjie; Lu, Shaokai; Shi, Benshan; Zheng, Haiping
Abstract : Purpose: The purpose of this paper is to provide a conceptual model for examining the effects of trust (competence trust, goodwill trust) and cooperation on partner opportunism and for exploring the moderating effects of guanxi on the relationships among trust, cooperation and opportunism in joint ventures. Design/methodology/approach: The sample for this paper comprises 981 manufacturing joint ventures from various industrial sectors. A total of 354 valid questionnaires were collected, representing a 36 per cent response rate. The conceptual model is tested with structural equation modeling adopting AMOS software. Findings: The empirical findings indicate that both competence trust and goodwill trust reduce partner opportunism in a joint venture through fostering cooperation. Competence trust also exerts significant influence on preventing opportunism, whereas opportunistic behavior is not greatly affected by goodwill trust. Additionally, the results reveal that guanxi helps strengthen the negative relationship between cooperation and opportunism. Originality value: This paper makes a threefold contribution: First, it investigates empirically the direct influence of two types of trust on partner opportunism. Second, it tests indirect influence of trust on partner opportunism through the path of cooperation. Third, it explores the moderating effects of guanxi in relationships on trust, cooperation and partner opportunism. Implications offers suggestions for management practice to reduce partner opportunism in joint-venture manufacturing.